2017
DOI: 10.1158/1055-9965.epi-16-0439
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Cancer—Moving Beyond BMI

Abstract: Body mass index (BMI) and simple counts of weight are easy and available tools in the clinic and in research. Recent studies have shown that cancer patients with low-normal BMI (or those with weight loss) have worse outcomes than obese patients. These results suggest that obesity has a protective effect and has been termed the ‘obesity paradox’. In this commentary, we discuss hypothetical explanations and take a step beyond BMI or simple weights alone to present other useful and more specific body composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 51 publications
4
69
0
1
Order By: Relevance
“…CT scans are readily available for colorectal cancer patients for both staging and surveillance, commercially available programs (25) are currently available to assess body composition, and abbreviated (43) and automated (44) assessment methods are emerging. In the era of precision medicine, we need to move beyond BMI and utilize more precise body composition techniques to assess muscle (45) mass, as well as directly measure adiposity to help to guide treatment plans to optimize survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…CT scans are readily available for colorectal cancer patients for both staging and surveillance, commercially available programs (25) are currently available to assess body composition, and abbreviated (43) and automated (44) assessment methods are emerging. In the era of precision medicine, we need to move beyond BMI and utilize more precise body composition techniques to assess muscle (45) mass, as well as directly measure adiposity to help to guide treatment plans to optimize survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index is an imprecise measure of body composition, and monitoring BMI changes may be insufficient to promptly identify occult body composition changes . We found that changes in SMI and TATI were weakly correlated with the change in BMI, and changes in SMD and SMG showed no correlation with the BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in body composition during cancer therapy have been associated with treatment‐related toxicity, physical inactivity, malnutrition, cancer invasiveness, and cancer therapy, which in turn could influence patient outcomes . Therefore, the prognostic value of body composition measurements in stage III EC needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Although increased body mass index (BMI) has been shown to be protective for some patients with cancer , there is evidence suggesting that obesity contributes to oncologic development and progression via chronic inflammation . It suffices to say that BMI is an imperfect biomarker of body composition as it relates to cancer outcomes . Recently, Young et al (2019) examined the role of skeletal muscle mass and adiposity on clinical outcomes in a cohort of patients with melanoma who received anti–programmed cell death protein 1 monotherapy.…”
Section: Discussionmentioning
confidence: 99%